Hubungan Rendahnya Pengetahuan Tentang Imunisasi Kanker Serviks Pada Wanita Usia Subur (WUS) Di RT 05 RW 02 Kelurahan Telaga Asih Bekasi Tahun 2023 - Dian Sapta Pebriani; Yulianti Yulianti (Jurnal Anestesi, 2024)
Globocan data for 2020 recorded that the total cancer cases in Indonesia in 2020 reached 396,914 cases and the total deaths were 234,511 cases. Cervical cancer (cervix) ranks second with 36,633 cases or 9.2% of total cancer cases. One of the factors that contributes to the high incidence of cervical cancer in Indonesia is the lack of awareness and access to routine examinations and vaccinations. Cervical cancer is one of the cancers that can be prevented, namely by immunization with the HPV vaccine and early detection of cervical cancer with a Pap smear or IVA examination (visual inspection using acetic acid). The aim of this research is to analyze factors related to WUS knowledge about the low level of Human Papilloma Virus (HPV) immunization in RT 05 RW 02, Telaga Asih Bekasi Village in 2023. The research method used is a cross sectional survey method. The population in this study was 50 female respondents of childbearing age in RT 05 RW 02. The sample was taken using a total sampling technique of 50 female respondents of childbearing age in RT 05 RW 02. Univariate analysis used frequency distribution and for bivariate tests used the Chi Square test. This research uses primary data from filling out questionnaires by respondents. Based on the results of the analysis of the 50 respondents, 31 people (62.0%) had the most good knowledge, 41 people aged 20-35 years (82.0%). There were 29 women whose parity was not at risk (58%), 29 people had at least high school education (58%), and 34 people got information sources electronically (68%). Variables related to knowledge are education and sources of information with a value of 0.000 < 0.05. Meanwhile, variables that are not related are age and parity. It is hoped that this research will become a reference for increasing knowledge and an intensive approach to WUS. The results of this research can also be used as an opener to wider insight into midwifery and especially in the field of reproductive health.